Writing on the Animal’s Side: Review of Éric Baratay, Animal Biographies: Toward a History of Individuals - Motamedi Fraser, Mariam (Humanimalia, 2023)
Review of: Éric Baratay, Animal Biographies: Toward a History of Individuals. Translated by Lindsay Turner. Animal Voices / Animal Worlds. Athens: University of Georgia Press, 2022. 240 pp. 28.95 (pb)